High proportion of tumor necrosis predicts poor survival in surgically resected high-grade neuroendocrine carcinoma of the lung. (July 2021) - Sugimoto, Akira; Umemura, Shigeki; Miyoshi, Tomohiro; Nakai, Tokiko; Kuroe, Takashi; Nosaki, Kaname; Ikeda, Takaya; Udagawa, Hibiki; Kirita, Keisuke; Zenke, Yoshitaka; Matsumoto, Shingo; Yoh, Kiyotaka; et al.
Highlights: Tumor necrosis has a negative impact on the survival of patients with cancer. The proportion of necrosis in the tumor tissues was able to be precisely quantified using digital image analysis. A high proportion of tumor necrosis (≥ 10 %) had a negative prognostic value in patients with surgically resected HGNEC. Abstract: Objectives: Tumor necrosis is a negative prognostic factor in various cancers. High-grade neuroendocrine carcinomas (HGNEC) of the lung, such as small cell lung cancer (SCLC) and large cell neuroendocrine carcinoma (LCNEC), commonly have histopathological features of tumor necrosis. However, the prognostic value of tumor necrosis remains unknown. Materials and methods: A total of 81 patients with HGNEC (SCLC, n = 42; LCNEC, n = 39) who underwent complete resection were enrolled. The proportion of necrosis in the tumor tissues was quantified using digital image analysis. We analyzed the relationship between the proportion of necrosis, clinicopathological factors, and prognosis. Moreover, we examined the correlation between genomic alterations and proportion of necrosis. Results: The median proportion of necrosis was 10.6 % (range, 0–62.8 %). The proportion of necrosis was not significantly different between SCLC (median, 5.1 %; range, 0–62.8 %) and LCNEC (median: 14.2 %; range, 0–59.3 %) ( p  =  0.14). The cumulative incidence of recurrence (CIR) and lung cancer-specific cumulative incidence of death (LC-CID) were significantly higher in patients with 10 % or higher necrosis (necrosis ≥ 10 %) than in those with less than 10 % (necrosis < 10 %) (hazard ratio [HR], 2.94; 95 % confidence interval [CI], 1.30–6.64, and HR, 2.87; 95 % CI, 1.13–7.29, respectively). In the bivariate analysis, necrosis ≥ 10 % was independently associated with higher CIR and tended to be associated with higher LC-CID. The frequency of genomic alterations in the PI3K/AKT/mTOR pathway, MYC family, MAPK/ERK pathway, and major RTK signaling pathways were not different between the necrosis ≥ 10 % and necrosis < 10 % groups for both SCLC and LCNEC. Conclusion: High proportion of tumor necrosis (≥ 10 %) had a negative prognostic value in surgically resected HGNEC.